Protection of Minority Share-Holders Rights - Waqas, Muhammad; Zeb, Aneela; Zeb, Alam (International Journal of Social Sciences and Management, 2015)
In this modern and advance era of competition, corporate sector plays an extremely important role in the development of a state by strengthening its economy and ensuring the economic stability. The corporations are controlled by the shareholders. In a corporation/company, minority shareholders also play a vital role in the business of the company. Laws have been formulated for the protection of the minority shareholders, however, these laws are not observed in its true spirit due to the ignorance of minority shareholders about their rights. The scope of this article is to review the status of minority shareholders and safeguards of minority shareholders’ rights. Int. J. Soc. Sci. Manage. Vol-2, issue-3: 193-196 DOI: http://dx.doi.org/10.3126/ijssm.v2i3.12745